Linear Widths of the Besov Classes of Periodic Functions of Many Variables. I - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain order estimates for linear widths of the Besov classes \(B_p,θ^r\) of periodic functions of many variables in the space L q for certain values of the parameters p and q.